Research handbook on climate disaster law : barriers and opportunities - Lyster, Rosemary, 1959-; Verchick, Robert R. M. (Research handbooks in climate law, 2018)
Climate change has thrust us into a "no-analog" future in which climate disasters threaten to cause extraordinary damage, with little precedent to guide policymakers and private actors. Addressing such risks requires a firm grounding in disaster risk reduction, climate change policy, and environmental law. This Research Handbook provides readers with that integrated foundation, investigating topics in international law as well as domestic programs from countries around the world. Because climate disasters affect both government and non-government actors, the Research Handbook covers issues of both public and private law. We know from the scientific literature and recent experience that the laws addressing natural disasters are insufficient to confront disasters amplified by climate change. The Research Handbook acknowledges that the majority of disasters are susceptible in some way to changes in the earth's climate and explores the barriers to, and opportunities for, finding legal solutions to the risks posed by such disasters. It shows that climate change must be considered in order to fully understand disaster risk and the respective legal and policy responses. The Research Handbook also emphasizes the moral responsibility we have to move as quickly as possible to create a carbon-free economy. This work will be of great appeal to legal scholars, practitioners, and policymakers who are interested in environmental law or climate change as it relates to international and domestic law and policy.